Experimental investigation of drying characteristics of cornelian cherry fruits (Cornus mas L.) - Ozgen, Filiz (Springer, 2015)
Major target of present paper is to investigate the drying kinetics of cornelian cherry fruits (Cornus mas L.) in a convective dryer, by varying the temperature and the velocity of drying air. Freshly harvested fruits are dried at drying air temperature of 35, 45 and 55 A degrees C. The considered drying air velocities are V (air) = 1 and 1.5 m/s for each temperature. The required drying time is determined by taking into consideration the moisture ratio measurements. When the moisture ratio reaches up to 10 % at the selected drying air temperature, then the time is determined (t = 40-67 h). The moisture ratio, fruit temperature and energy requirement are presented as the functions of drying time. The lowest drying time (40 h) is obtained when the air temperature is 55 A degrees C and air velocity is 1.5 m/s. The highest drying time (67 h) is found under the conditions of 35 A degrees C temperature and 1 m/s velocity. Both the drying air temperature and the air velocity significantly affect the required energy for drying system. The minimum amount of required energy is found as 51.12 kWh, at 55 A degrees C and 1 m/s, whilst the maximum energy requirement is 106.7 kWh, at 35 A degrees C and 1.5 m/s. It is also found that, air temperature significantly influences the total drying time. Moreover, the energy consumption is decreasing with increasing air temperature. The effects of three parameters (air temperature, air velocity and drying time) on drying characteristics have also been analysed by means of analysis of variance method to show the effecting levels. The experimental results have a good agreement with the predicted ones.
Keywords: Energy Requirement; Taguchi Method; Fluidized-Bed; Potato Slices; Microwave; Dryer; Air; Optimization; Dehydration; Parameters